In response to the article entitled “Surgery for recurrent lower lip carcinoma” by Maharjan S et al, published in KUMJ, 2008 Vol. 6, No. 3, Issue 23, 375-378. - Bhandary, S (Kathmandu University Medical Journal, 2009)
doi: 10.3126/kumj.v7i1.1774 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 86-88